Penerapan Model Pembelajaran Role Playing Untuk Meningkatkan Hasil Belajar Siswa di Kelas V SD Negeri 22 Banda Aceh - Aslah, Hauratul; Rani, M. Isa; Anwar, Faisal (Journal of Technology and Literacy in Education, 2023)
Teachers tend to teach learning using the lecture method which makes students feel bored and bored. Students feel bored and lack of attention when learning is in progress so as to reduce student interest and motivation. The role playing model learning method is one model that can make students active, independent, fun and able to form good cooperation between teachers and students, between students and other students. The purpose of this study was to find out the application of the Role Playing model in improving Student Learning Outcomes in Class V SD Negeri 22 Banda Aceh for the 2021/2022 Academic Year. The research population was all fifth grade students at SD Negeri 22 Banda Aceh for the 2022/2023 academic year, totaling 85 students. The research sample was class V-c (28 students), as a technique for collecting observational data, tests, data processing techniques using the t-test. The results showed that the research was conducted at SD Negeri 22 Banda Aceh, when viewed from the hypothesis testing it was carried out at a significant level α = 0.05 and based on the results of the study obtained tcount = 49.54 and ttable = 1.67. This shows that the value of tcount> ttable and concludes that the alternative hypothesis (Ha) reads ". Well received. Hypothesis (Ha) which reads "Using the Role Playing model can improve the Learning Outcomes of Class V Students at SD Negeri 22 Banda Aceh.